Cultural Barriers to Equality: Eco-Discursive Frames Against the Woman’s Search for Self in Lola’s The Lock On My Lips - Fomukong, Seino Evangeline Agwa (Advances in Social Sciences Research Journal, 2023)
In the North West Region of Cameroon especially, the traditional law on land ownership supplants that of the constitution of Cameroon which gives equal rights to men and women. Consequently, a married woman does not own land as per the customary law in most of the rural areas of this part of the country. In The Lock on My Lips, the news of a woman having a land certificate ignites conflict in Kibaaka, a rural community that is predominantly agrarian. The women led by Mrs Ghamogha resist this tradition against Ability and other men who try to preserve this aspect of the culture. Perpetua Lola presents a cultural arena that acts in defining the eco-linguistic choices made in the text. This study examines the exploration of the ideology of social power through the effect of the ecological context on language and its role in a gender biased context. The paper uses the survey research design, identifying and describing the lexico-semantic patterns and the discourse forms of the text representing plants, animals and diseases with the socially constructed sacrilege of a woman owning a piece of land. Ruth Wodak’s Discourse-Historical approach is used in conjunction with Teun van Dijk’s Socio-Cognitive approach, to examine how women are referred to linguistically through referential, predication, argumentation, framing and intensification discursive strategies. The study concludes that discourse constitutes society and culture, with some ideologies behind it portraying unequal power relations which Lola fights against in the text.